Incommunicated: spiritual isolation in Dostoieviski and his eco in the narrative of Carson McCullers - Díez Bosch, Miriam; Micó Sanz, Josep-Lluís; Sabaté Gauxachs, Alba (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
Fyodor Dostoevsky (1821-1881) tears the human soul to the point of leaving it wounded by suffering, guilt and isolation. And yet, defeat does not win the battle. Southern American writer Carson McCullers (1917-1967) writes about the loneliness and misery of the southern United States with an attentive look at the desolate landscapes of Fyodor Dostoevsky’s Russia, not only physical but essentially metaphysical. This author who already read the Russian teacher at age 13 explores the human entrails from rural, desolate, inhospitable and unfortunate, with racial differences, overexposure of alcohol and a concept of internal moral good that appears as a constant and inexhaustible drive. In this approach we want to highlight how the mystery of evil, but also the act of will and incommunication are aspects that unite both authors, especially in two of his masterpieces, Crime and Punishment and The Heart is a Lonely Hunter, respectively.